Risk-related 18F-FDG PET/CT and new diagnostic strategies in patients with solitary pulmonary nodule: the ITALIAN multicenter trial - Spadafora, Marco; Pace, Leonardo; Evangelista, Laura; Mansi, Luigi; Del Prete, Francesco; Saladini, Giorgio; Miletto, Paolo; Fanti, Stefano; Del Vecchio, Silvana; Guerra, Luca; Pepe, Giovanna; Peluso, Giuseppina; et al. (European journal of nuclear medicine and molecular imaging, 2018)
Purpose Diagnosis of solitary pulmonary nodule (SPN) is an important public health issue and 18 F-FDG PET/CT has proven to be more effective than CT alone. Pre-test risk stratification and clinical presentation of SPN could affect the diagnostic strategy. A relevant issue is whether thoracic segmental (s)-PET/CT could be implemented in patients with SPN. This retrospective multicenter study compared the results of FDG whole-body (wb)-PET/CT to those of s-PET/CT. Methods 18 F-FDG PET/CT of 502 patients, stratified for pre-test cancer risk, were retrospectively analyzed. The thoracic part of wb-PET/CT, considered s-PET/CT, was compared to wb-PET/CT. Clinical and PET/CT variables were investigated for SPN characterization as well as for identification of patients in whom s-PET/CT could be performed. Histopathology or follow-up data were used as a reference. Results In the study population, 36% had malignant, 35% benign, and 29% indeterminate SPN. 18 F-FDG uptake indicative of thoracic and extra-thoracic lesions was detectable in 13% and 3% of the patients. All patients with extra-thoracic metastases ( n = 13) had thoracic lymph node involvement and highest 18 F-FDG uptake at level of SPN (negative predictive value 100%). Compared to wb-PET/CT, s-PET/CT could save about 2/3 of 18 F-FDG dose, radiation exposure or scan-time, without affecting the clinical impact of PET/CT. Conclusion Pre-test probability of malignancy can guide the diagnostic strategy of 18 FDG-PET/CT in patients with SPN. In subjects with low-intermediate pretest probability s-PET/CT imaging might be planned in advance, while in those at high risk and with thoracic lymph node involvement a wb-PET/CT is necessary.